Effects of aquatic exercise on insulin-like growth factor-1, brain-derived neurotrophic factor, vascular endothelial growth factor, and cognitive function in elderly women - Kang, Doo-wang; Bressel, Eadric; Kim, Do-yeon (Experimental gerontology, 2020)
The purpose of this study was to investigate the effects of a 16-week aquatic exercise program on brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1), and vascular endothelial growth factor (VEGF) levels, as well as cognitive function in elderly women. The subjects were 20 elderly women aged 68–80 years, randomly divided into an aquatic exercise group (n = 10) and a control group (n = 10). The aquatic exercises were performed for 60 min, three times per week for 16 weeks, and the intensity was progressively increased every 4 weeks (40–50% of heart rate reserve (HRR) for weeks 1–4, 50–60% of HRR for weeks 5–8, 60–65% of HRR for weeks 9–12, and 65–70% of HRR for weeks 13–16). The data were analyzed using two-way repeated measures analysis of variance, paired t-test, and independent t-test with an alpha level to indicate significance set at.05 for all tests. After the 16-week aquatic exercise program, the BDNF and IGF-1 levels (p < .01, respectively), and cognitive function (p < .05) of the aquatic exercise group showed significant changes. BDNF, IGF-1, and cognitive function levels (p < .01, respectively) were significantly different between the aquatic exercise group and control group. The results of this study suggest that regular aquatic exercise in elderly women during the early stages of aging can increase the expression of BDNF and IGF-1, thus maintaining and improving cognitive function. •The aquatic exercise decreased the VEGF expression in fat cells by decreasing body fat mass.•Exercise intensity must be appropriate to lead to an increase BDNF and IGF-1 levels.•Cognitive function can be maintained and improved by increasing the expression of neurotrophic factors through regular aquatic exercise.